2013
DOI: 10.1179/1743275814y.0000000042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of iron ore characterisation using a scanning electron microscope and optical image analysis

Abstract: In order to develop downstream processing routines for iron ore and to understand the behaviour of the ore during processing, extensive mineralogical characterisation is required. Microscopic analysis of polished sections is effective to determine mineral associations, mineral liberation and grain size distribution. There are two main imaging techniques used for the characterisation of iron ore, i.e. optical image analysis (OIA) and scanning electron microscopy (SEM). In this article, a QEMSCAN system is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“…In this work, the authors reported segmentation of a mineral whose reflectivity area partially overlapped with the reflectivity area of epoxy. In these cases, the capability of some software packages to identify different textures can be utilized (see Donskoi et al, 2011Donskoi et al, , 2013a. In this example, the whole mineral reflectivity area is overlapped by some minor, extra differentiated areas.…”
Section: Automated Identification Of Particles and Opaque Mineralsmentioning
confidence: 99%
“…In this work, the authors reported segmentation of a mineral whose reflectivity area partially overlapped with the reflectivity area of epoxy. In these cases, the capability of some software packages to identify different textures can be utilized (see Donskoi et al, 2011Donskoi et al, , 2013a. In this example, the whole mineral reflectivity area is overlapped by some minor, extra differentiated areas.…”
Section: Automated Identification Of Particles and Opaque Mineralsmentioning
confidence: 99%
“…On the other hand, OIA-based automated mineralogy has the lower cost and is less time demanding. CSIRO (Donskoi et al, 2013) has developed an OIA-based automated mineralogy which has been used for iron ore characterization. In high grade samples, the OIA system results were close to the SEM-based automated mineralogy (QEMSCAN), but in lower grade samples and low resolutions the OIA results were drifting away from true values (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[9]), has better resolution for massive screening and better characterises porosity (for detailed comparison of the two techniques see Refs. [3,12]). …”
Section: mentioning
confidence: 99%
“…4 (reproduced from Ref. [12]) demonstrates the automated segmentation of two different types of hematite-martite and micro platy hematite-that have the same reflectivity but different morphology/texture. This feature can also be used for the segmentation of different morphologies of hematite and SFCA in iron ore sinter and IMDC (inert maceral derived components) and RMDC (reactive maceral derived components) in metallurgical coke.…”
Section: Mineral 4/recognition 4 Softwarementioning
confidence: 99%